SIKAP DAN KEPUASAN KONSUMEN AYAM PROBIO DI KOTA METRO DAN BANDAR LAMPUNG - Ellenia Agustia D S; Dwi Haryono; Adia Nugraha (Lampung University, 2020)
This study aims to determine the characteristics, stages of decision making, attitudes, and the level of consumer satisfaction on consuming probio chicken. The research location was determined purposively at probio chicken farm of Kelompok Peternak Ayam (KPA) Berkat Usaha Bersama (BeUBe) 21C Yosomulyo Metro, Transmart, Giant Kedaton and Carrefour in Bandar Lampung. The research was conducted as a survey, in which total sample constituted of 30 people recruited using accidental sampling technique. Data were collected by interviewing using questionnaires and analyzed by using descriptive analysis, Multiatribute Fishbein, and Consumer Satisfaction Index (CSI). The results showed that most consumers were women (60%). The highest frequency of purchasing probio chicken was once a month (36.67%). Consumer's decision-making stages showed that consumers bought probio chicken meat to meet their needs of improving nutrition. Consumers’ purchase was influenced by their family in which influencing factors were chicken taste and quality. Based on the analysis of consumer attitudes using Fishbein multiattribute model, it showed that multiatribute of attitude scores (Ao) equal to 157.83 and flavor attributes was become the highest score (22.09). Based on CSI, the level of customer satisfaction was 83.51%, in the scale range 0.81 to 1.00; meaning that consumers were very satisfied on consuming probio chicken.Key words: attitude, probio chicken, satisfaction